Utilization of Activated Carbon/Magnesium(II) Composites in Decreasing Organic Materials - Ullica, Dheasi Rani; Zaharah, Titin Anita; Silalahi, Imelda Hotmarisi (Universitas PGRI Madiun, 2023)
This study aimed to determine the characteristics, adsorption capacity, and isotherm of the adsorbent AC/Mg(II) composite in decreasing organic matter in peat water. Activated carbon was produced from empty fruit bunches of oil palm containing high levels of lignocellulose. Carbon was synthesized through the carbonization process and then activated with CH3COONa. The activated sample was composited with magnesium nitrate hexahydrate through an in-situ method under alkaline conditions using NaOH. The adsorbent AC/Mg(II) composite that had been prepared was characterized using FTIR, showing the presence of Mg-O bonds at the absorption wave number of 403.12 cm-1. The results showed that the moisture content of the adsorbent was lower compared to activated carbon, namely 1.30%. Furthermore, the best mass was 2 g AC/Mg(II) with an adsorption of 2.26 mg/g and an organic matter adsorption percentage of 14.41%. Furthermore, the optimum contact time was 15 minutes with an adsorption of 2.42 mg/g and a percentage of 17.15%. The mechanism occurring in the AC/Mg(II) composite with peat water organic matter followed the Langmuir isotherm equation, which formed a monolayer. The equation gave R2, adsorption capacity (Qo), and adsorption constant (k) values of 0.9994, 0.2340 mg/g, and 0.0047, respectively.